2014
DOI: 10.2169/internalmedicine.53.2065
|View full text |Cite
|
Sign up to set email alerts
|

Marked and Rapid Regression of Hepatic Amyloid Deposition in a Patient with Systemic Light Chain (AL) Amyloidosis after High-dose Melphalan Therapy with Stem Cell Transplantation

Abstract: A 52-year-old woman with a high serum alkaline phosphatase (ALP) level underwent a liver biopsy, which showed diffuse heavy deposition of Aκ amyloid, and was diagnosed as having immunoglobulin light chain (AL) amyloidosis. Although she received high-dose melphalan with stem cell transplantation and achieved a hematologic complete response (CR), her ALP level began to increase one year after treatment. Further examinations revealed that she was still in a CR state with dominant bone-type ALP, and re-biopsied li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
5
0
2
Order By: Relevance
“…Asian and European patients with Aα-chain amyloidosis do not show remarkable differences with respect to clinical manifestations; however, the most prevalent genetic variant E526V in European patients may not be common in Asian patients. Recently, several effective therapies have been established for treating different types of systemic amyloidosis; however, the therapeutic strategy for treating each type of amyloidosis is different [ 13 , 17 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] ( Table 2 ), highlighting the importance of the correct diagnosis of the disease at an early stage. Moreover, the possibility of Aα-chain amyloidosis should always be considered in sporadic cases of amyloid nephropathy, even in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…Asian and European patients with Aα-chain amyloidosis do not show remarkable differences with respect to clinical manifestations; however, the most prevalent genetic variant E526V in European patients may not be common in Asian patients. Recently, several effective therapies have been established for treating different types of systemic amyloidosis; however, the therapeutic strategy for treating each type of amyloidosis is different [ 13 , 17 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ] ( Table 2 ), highlighting the importance of the correct diagnosis of the disease at an early stage. Moreover, the possibility of Aα-chain amyloidosis should always be considered in sporadic cases of amyloid nephropathy, even in Asian countries.…”
Section: Discussionmentioning
confidence: 99%
“…However, most of them may have been misdiagnosed with other types of systemic amyloidosis. Recently, several effective therapies have been established, especially for AL amyloidosis or AA amyloidosis (27)(28)(29). In AApoAI amyloidosis, organ transplantation, including that of the kidney, liver, or heart, has been performed as a promising therapy (30).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of amyloid fibrils is a dynamic process, with monomers and oligomers being rapidly exchanged for each other depending on various factors that include pH, temperature, and co-solvents [ 34 ]. According to studies of serial biopsy specimens obtained from AL, ATTR, and AA amyloidosis patients, even mature amyloid fibril masses disappear when successful disease-modifying therapies are provided [ 35 , 36 , 37 ]. Electron microscope studies have demonstrated the appearance of dotty or globular structures 4 to 5 nm in diameter and the subsequent formation of short protofibrils 30 to 100 nm in length during an incubation of Aβ in vitro [ 38 ].…”
Section: Initiation Of Protein Aggregationmentioning
confidence: 99%